Penanaman Nilai-Nilai Moderasi Beragama Dalam Pendidikan Agama Islam Perspektif Nurcholish Madjid - Rikil Amri; Agung Indarto; Burhanudin Raya Rambani (PROSIDING SENANTIAS: Seminar Nasional Hasil Penelitian dan Pengabdian kepada Masyarakat, 2025)
This research is based on several conflict events that occurred in Indonesia. This shows the vulnerability of a pluralistic society to experiencing tension and conflict. Religious moderation is an attitude to create harmony between religious believers. This research aims to describe religious moderation from Nurcholish Madjid’s perspective which includes (1) the understanding and concept of religious moderation in general (2) the values ​​of religious moderation from Nurcholish Madjid’s perspective (3) instilling the values ​​of religious moderation from Nurcholish Madjid’s perspective in Islamic Religious Education. Education is part of a tool for social control. So a social problem is an important part to pay attention to. Including tensions and conflicts related to religion. Religious moderation in Islamic Religious Education is expected to be able to encourage harmonization in social life. Nurcholish Madjid as a thought reformer in Indonesia is known to be concerned with Islamic and Indonesian studies. This research tries to trace the footsteps of Nurcholish Madjid’s thoughts regarding religious moderation in Islamic education. The results of this research obtained several conclusions, including; (1) Religious moderation is a concept of multicultural awareness among religious adherents to create harmony in society. (2) Nurcholish Madjid’s perspective of religious moderation has several values, namely the spirit of monotheism and inclusive theology; pluralism; and tolerance. (3) The application of religious moderation from Nurcholish Madjid’s perspective in Islamic Religious Education must consider ideal education. According to Nurcholish Madjid, the ideal Islamic religious education is one that builds an environment of inclusion, liberation, intellectualism and modernity.